Symmetric and Transitive Registration of Image Sequences - Škrinjar, Oskar; Bistoquet, Arnaud; Tagare, Hemant (International Journal of Biomedical Imaging, 2008)
This paper presents a method for constructing symmetric and transitive algorithms for registration of image sequences fromimage registration algorithms that do not have these two properties. The method is applicable to both rigid and nonrigid registrationand it can be used with linear or periodic image sequences. The symmetry and transitivity properties are satisfied exactly (up tothe machine precision), that is, they always hold regardless of the image type, quality, and the registration algorithm as long asthe computed transformations are invertable. These two properties are especially important in motion tracking applications sincephysically incorrect deformations might be obtained if the registration algorithm is not symmetric and transitive. The method was tested on two sequences of cardiac magnetic resonance images using two different nonrigid image registrationalgorithms. It was demonstrated that the transitivity and symmetry errors of the symmetric and transitive modification of thealgorithms could be made arbitrary small when the computed transformations are invertable, whereas the corresponding errorsfor the nonmodified algorithms were on the order of the pixel size. Furthermore, the symmetric and transitive modification of thealgorithms had higher registration accuracy than the nonmodified algorithms for both image sequences.